Wits and Interpretation Keyboard Thoughts - Edlund, Bengt (Peter Lang International Academic Publishing Group, 2023)
In what ways can analytic reection be of avail when engaging in music as a musician? What restrictions of the interpreter's freedom do musical scores impose? Which licences do musicians in fact allow themselves? Can hierarchical tonal analysis really guide musicians towards artistically rewarding interpretations? Or is perhaps a painstaking and sensitive study of the musical details, revealing continuous processes, a more productive path to telling performances? roughout the book, the views and discussions are amplied by music examples.